You are on page 1of 14

# Regular Singular Points: Method of Frobenius Regular Singular Points: Method of Frobenius

## Remark: This theorem fails to answer the question of

h fi d h d l i h h diff how to find the second solution when the difference m
1
-
m
2
is zero or a positive integer.
There are three cases: There are three cases:
CASE A: If m
1
= m
2
there can not exist a second
Frobenius series solution Frobenius series solution.
For the other two cases we see the formula replacing m by
mm
2
2 0 2 1 2 1 1
( ) ( ) [( 1) ]
n n n n
a f m n a m p q a m n p q

+ = + + +
Anil Kumar, Department of Mathematics 39
Regular Singular Points: Method of Frobenius Regular Singular Points: Method of Frobenius
Difficulty in calculating a
n
arises because f(m
2
+n)=0 for
some +ve integer n.
CASE B: If the right side of the previous equation is not
zero when f(m
2
+n) = 0, then no way of continuing the
calculation of the coefficients and there cannot exist a calculation of the coefficients and there cannot exist a
second Frobenius series solution.
CASE C: If the right side of the equation happens to be
h f( ) 0 h d d b zero when f(m
2
+n) = 0, then a
n
is unrestricted and can be
assigned any value whatever.
In particular we can put a = 0 and continue to In particular, we can put a
n
0 and continue to
compute the coefficients without further difficulties.
Hence in this case there does exists a 2
nd
Frobenius series
l i
Anil Kumar, Department of Mathematics 40
solution.
The form of 2 The form of 2
nd nd
solution when m solution when m
11
-- mm
22
= 0 or a + = 0 or a +ve ve
integer integer integer integer
Define a +ve integer k = m
1
- m
2
+1, the indicial equation
can be written as can be written as
So equating the coefficients of m we get
, 0 ) ( ) )( (
2 1 2 1
2
2 1
= + + = m m m m m m m m m m
So equating the coefficients of m, we get
or
and we have
) ( 1
2 1 0
m m p + =
, 1
1 0 2
m p m =
2 p m k + and we have
Then we can find a second solution y
2
from the known
solution
0 1
2 p m k + =
( )
2
solution
By writing
vy y =
( ) + + + =
2
2 1 0 1
1
x a x a a x y
m
Anil Kumar, Department of Mathematics 41
By writing
1 2
vy y =
22
nd nd
solution solution
Where
1 ) (
2
1
e
y
v
dx x P
}
=
'

) (
1 ) ) / ((
2
1 0
2
1
1 0
1
e
x a a x
dx p x p
m
}
+ +
=
+ +

) (
1
) log ( (
2
1 0
2
1 0
1
e
x a a x
x p x p
m
+ +
=

). (
1
) (
1
) (
2
1 0
2
1
1
x g
x
e
x a a x
k
x p
m
=
+ +
=

## The function g(x) defined by the last equality is clearly

analytic at x = 0 with
/ 1 ) 0 (
2
Anil Kumar, Department of Mathematics 42
y
, / 1 ) 0 (
2
0
a g =
22
nd nd
solution solution
So in some interval about the origin we have
0 ) (
2
= + + + b x b x b b x g
It follows that
. 0 , ) (
0 2 1 0
= + + + = b x b x b b x g
+ + + + + =
'
+ k k
b x b x b x b v
1 1
so
+ + + + + =
k k
b x b x b x b v
1 1 0
1 2
0 1
1
log
1 2
k k
k k
b x b x
v b x b x
k k
+ +

= + + + + +
and
1
g
1 2
k k
k k + +
1 2 k k
b b
+ +
| |
1 2
0 1
2 1 1 1
log
1 2
k k
k k
b x b x
y y v y b x b x
k k
+ +

| |
= = + + + + +
|
+ +
\ .

Anil Kumar, Department of Mathematics 43
22
nd nd
solution solution
Thus we get
1
2 1
1 1
0 1
1 1 0 1
log ( ) .
k k
m
k
y y v
b x b x
b y x x a a x
+ +
=
| |
= + + + + +
|

1 1 0 1
g ( )
1 2
k
y
k k
|
+ +
\ .
If we factor x
-k+1
out of the series last written, use If we factor x out of the series last written, use
m
1
k +1 = m
2
and multiply the two remaining series, then we obtain
2
log
m n
y b y x x c x

= +

Anil Kumar, Department of Mathematics 44
2 1 1
0
log
k n
n
y b y x x c x

=
= +

Remark: Remark:
0 b b
I. If m
1
= m
2
, then k =1 and
Therefore, in this case i.e. Case A, log x is definitely
t i th d l ti
1 0
0.
k
b b

= =
present in the second solution.
ii. if m
1
- m
2
= k - 1 is a +ve integer, then sometimes
and the logarithmic term is present (Case
0 = b
and the logarithmic term is present (Case
B), and sometimes b
k-1
= 0 and there is no logarithmic
term i.e. Case C.
0
1
=
k
b
Anil Kumar, Department of Mathematics 45
Remark Remark
The practical difficulty is that we have no direct means
of calculating the coefficients for y
2
and the method of g y
2
Frobenius is partly successful (for CASE A and B),
the general form of a second solution is
2
2 1
0
log
m n
n
y y x x c x

= +

where the c
n
are certain unknown constants that can
0 n =
n
be determined by substituting the above series directly
into the differential equation.
Anil Kumar, Department of Mathematics 46
Example: Example:
Solve the following differential equation
2 2
When p = 0, Bessels equation is
2 2
4 4 0, 0. x y x y y x
'' '
+ + = >
h h d l h l d
2 2
0 x y xy x y
'' '
+ + =
show that its indicial equation has only one root, and
corresponding to this root the following is the Frobenius
series solution
2
2 2
0
( 1)
.
2 ( !)
n
n
n
n
y x
n

## Anil Kumar, Department of Mathematics 47

0
( )
n
Anil Kumar, Department of Mathematics 48
Anil Kumar, Department of Mathematics 49
Anil Kumar, Department of Mathematics 50
Anil Kumar, Department of Mathematics 51
Anil Kumar, Department of Mathematics 52